Вибрация и защита от нее - Суворов Герман (Библиотека журнала "Охрана труда и социальное страхование", 2001)
Экземпляры: КХ (20021023) / Инвентарный номер: 1046022 / Цена: / Сис.шифр: 51.24 / Авт.знак: С 89 / ГРНТИ: 76 / ББК: 51.244